2016
DOI: 10.1139/cjm-2015-0226
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of yeasts associated with plants growing in heavy-metal- and arsenic-contaminated soils

Abstract: Yeasts were quantified and isolated from the rhizospheres of 5 plant species grown at 2 sites of a Mexican region contaminated with arsenic, lead, and other heavy metals. Yeast abundance was about 10(2) CFU/g of soil and 31 isolates were obtained. On the basis of the phylogenetic analysis of 26S rRNA and internal transcribed spacer fragment, 6 species were identified within the following 5 genera: Cryptococcus (80.64%), Rhodotorula (6.45%), Exophiala (6.45%), Trichosporon (3.22%), and Cystobasidium (3.22%). Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…In recruiting the ectomycorrhizal fungal genera, the PhytOakmeter trees may have been targeting such an important contribution to the host plant health. Compared to the tree root-free zone, PhytOakmeter root zone was also enriched in yeast genera Phaeococcomyces (Butler et al, 2004), Sporobolomyces (Wang et al, 2015), Cystobasidium (Ramos-Garza et al, 2015;Yurkov et al, 2015), and Cyphellophora (Feng et al, 2014). Yeasts are essential in ecological processes involving mineralization of organic matter (Botha, 2011).…”
Section: Differences In Microbial Community Composition Between Soilsmentioning
confidence: 99%
“…In recruiting the ectomycorrhizal fungal genera, the PhytOakmeter trees may have been targeting such an important contribution to the host plant health. Compared to the tree root-free zone, PhytOakmeter root zone was also enriched in yeast genera Phaeococcomyces (Butler et al, 2004), Sporobolomyces (Wang et al, 2015), Cystobasidium (Ramos-Garza et al, 2015;Yurkov et al, 2015), and Cyphellophora (Feng et al, 2014). Yeasts are essential in ecological processes involving mineralization of organic matter (Botha, 2011).…”
Section: Differences In Microbial Community Composition Between Soilsmentioning
confidence: 99%
“…In recent years, due to increased interest in the problems of environmental safety and sustainable functioning of urban ecosystems, domestic and foreign works devoted to the study of soil biota more and more often consider issues of structural and functional transformations of communities of soil microorganisms due to anthropogenic influences of different quality and intensity. Household soil pollution is considered as one of the most serious instances for the violation of the "purity" of the city [1,7,12,21]. Our study of urban soils performed in 2019 in southern cities of Russia with different intensities of anthropogenic impact (Sochi, Simferopol, Krasnodar, and Maykop) showed that in the 0-10 cm layer on the territory of the largest (Krasnodar) and large (Simferopol, Sochi) cities, bacterial complexes changed and representation of the Enterobacteriaceae and Enterococcaceae families increased [4].…”
Section: Introductionmentioning
confidence: 99%
“…Trichosporon is a genus of anamorphic basidiomycetous yeast which is widely distributed in temperate and tropical areas, rotting wood, sludge, soil, mushrooms, plants, leaf-cutting ants, birds, and mammals (Obana et al 2010). Trichosporon yeasts were isolated from rhizospheres contaminated with heavy metals (Ramos-Garza et al 2016). The genus Trichosporon is a medically important yeast that includes a number of species causing both deep-seated and superficial infections.…”
Section: Introductionmentioning
confidence: 99%